Sociotropic personality traits positively correlate with the severity of social anxiety - (:unkn) unknown (SA MEDICAL ASSOC HEALTH & MEDICAL PUBL GROUP, 2015)
Aim. To investigate sociotropic-autonomic personality characteristics and their clinical implications in social anxiety disorder (SAD). Methods. The study included 68 consecutive patients who were either being followed up on an outpatient basis or presented for the first time to the psychiatric clinics of Bakirkoy Research and Training Hospital for Psychiatry, Neurology and Neurosurgery or Trakya University School of Medicine between May 2012 and May 2013, and were diagnosed primarily with generalised SAD according to Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) diagnostic criteria. Beck Depression Inventory (BDI), Sociotropy-Autonomy Scale (SAS), Symptom Checklist-90-R (SCL-90-R), Liebowitz Social Anxiety Scale (LSAS) and a sociodemographic data collection form designed by the authors were used as primary assessment instruments. Results. The mean age (standard deviation (SD)) of the sample group was 23.73 (8.85) years; 37 (54.4%) were female and 31(45.6%) were male. LSAS mean (SD) total fear score was 63.51 (13.74), mean total avoidance score was 61.24 (14.26), BDI mean score was 16.99 (9.58), SAS mean sociotropy score was 71.06 (16.79), and mean autonomy score was 63.22 (16.04). A statistically significant positive correlation was found between SAS sociotropy scores and LSAS fear and avoidance total scores, BDI scores and all subscales of SCL-90-R (p<0.01). There were no statistically significant correlations between SAS autonomy scores and LSAS fear and avoidance total scores, BDI scores and all subscales of SCL-90-R (p>0.05). Conclusion. Sociotropic personality characteristics in patients with SAD have been found to positively correlate with depression and social anxiety levels. Addressing this finding during treatment sessions and helping the patient increase flexibility in appraisal of social life events may have a positive impact on treatment outcome.
Keywords: DEPRESSION; AUTONOMY; DIMENSIONS; VULNERABILITY; SYMPTOMS; LIFE